Management of Economic Research in Russian Universities: Scientometrics and International Rankings - A. E. Shastitko; A. L. Zyubina (Мир новой экономики, 2019)
The authors analyse the environment and its current state of academic research in the field of economics formed in Russia. We considered the publication activity over the past six years of Russian economic, educational organisations as well as the results of the leading Russian universities in the QS and THE subject rankings. Further, we also revealed the connections between the formed conditions in which Russian economics researchers have to work and the results of universities in these rankings. The authors presume the need for expanding approaches to promote Russian economic science on the world stage. Therefore, we discussed current ways of stimulation and evaluation of the activities of Russian economic researchers and proposed that educational system governors use now need to be evaluated and perhaps improved.